KARYA SENI SANGGIT: PERJUMPAAN TRADISI MODERN DALAM PARADIGMA KEKARYAAN SENI RUPA - Kartika, Sony Dharsono (LPPM Universitas PGRI Adi Buana Surabaya, 2018)
The encounter of modern tradition is a paradigm of modern art with a touch of tradition, a phenomenon tosearch for Indonesian roots in Indonesian cultural identity, then called the work of sanggit. To meet the global era, thealternative we have to build is how to do local studies (traditional arts) that can be an alternative to the development ofart towards global ideology, so that global phenomena will become more local. Preservation of traditional art, as a formof cultural resilience. Preservation can be interpreted as preservation and conservation. Preservation is maintaining,caring for, and protecting, while conservation is the preservation of development and / or utilization of value. Thepurpose of this discussion is to offer a phenomenon of meeting modern traditions in the Indonesian art workforce paradigm; (1) offering the concept of revitalization of sanggit as the basis for art work, (2) offering the concept of reinterpretation of sanggit as the basis for art work and (3) offering the concept of symbolic expression and / or abstraction as the basis of art work. Research / study steps are carried out with a qualitative research model with a cultural approach, referring to the teachings of Javanese culture in accordance with Javanese cultural philosophy and philosophy. This approach emphasizes data interpretation in case specificity. The review of the analysis in this study emphasizes more on the interaction model of qualitative data analysis, using a Javanese cultural approach. Analysis interactions were carried out to analyze qualitative data from the results of empirical data collection. The interactive results of the analysis are then examined by interpretive analysis in a hermeneutic manner.